Genome-wide profiling of alternative splicing in Alzheimer's disease - Lai, Mitchell K.P. (Genom Data, 2014)
Alternative splicing is a highly regulated process which generates transcriptome and proteome diversity through the skipping or inclusion of exons within gene loci. Identification of aberrant alternative splicing associated with human diseases has become feasible with the development of new genomic technologies and powerful bioinformatics. We have previously reported genome-wide gene alterations in the neocortex of a well-characterized cohort of Alzheimer's disease (AD) patients and matched elderly controls using a commercial exon microarray platform [1]. Here, we provide detailed description of analyses aimed at identifying differential alternative splicing events associated with AD.